Fertility and sexuality of women with inflammatory arthritis. (August 2020) - Bourg, Mona; Ruyssen-Witrand, Adeline; Bettiol, Célia; Parinaud, Jean
Abstract: Objective: This study aimed to evaluate the impact of the four main types of inflammatory arthritis (rheumatoid arthritis (RA), ankylosing spondylitis (AS), psoriatic arthritis (PA), juvenile chronic arthritis (JCA)) on female fertility. Design: We performed a monocentric observational study, which took place in the Reproductive Medicine Department and the Rheumatology Department of the Toulouse University Hospital. An anonymous questionnaire was sent to patients aged 18–50 with RA, AS, PA or JCA who were diagnosed before the age of 40 and who consented to participate in the study. A section of the questionnaire was completed using the medical file of each patient. Results: Of the 521 eligible patients, 202 (39 %) answered the questionnaire. Before being diagnosed with a rheumatic disease, 87 % of patients with a desire for pregnancy had a spontaneously obtained live birth, compared to 75 % after (P < 0.05). However, this decrease only concerned RA (90 % before diagnosis vs 68 % after; P < 0.05). This difference was due to a lower rate of pregnancies achieved, but the number of miscarriages did not increase. Moreover, for patients who managed to conceive, the time required for conception did not increase, regardless of the type of rheumatic disease they had. Two thirds of patients reported a decrease in the frequency of sexual intercourse after diagnosis, mainly (75 %) because of the pain relating to the disease. Conclusion: Our study shows a trend of decreased fertility in patients with RA, perhaps due to sexual problems, while no impact of AS and PA on the ability to conceive was found. This impact on fertility didn't seem to be related to the decrease of sexuality. Multidisciplinary care including treatment from a rheumatologist, gynecologist and sexologist would appear essential in order to provide RA patients with the necessary information concerning their fertility, answer their questions about pregnancy and thus optimize their care.